Chemical Speciation of Uranium(VI) in Marine Environments: Complexation of Calcium and Magnesium Ions with [(UO2)(CO3)3]4− and the Effect on the Extraction of Uranium from Seawater. Issue 44 (11th September 2014) - Endrizzi, Francesco; Rao, Linfeng
Abstract The interactions of Ca2+ and Mg2+ with [UO2(CO3)3]4− were studied by calcium ion selective electrode potentiometry and spectrophotometry. The stability constants of ternary Ca‐UO2‐CO3 and Mg‐UO2‐CO3 complexes were determined with calcium ion selective electrode potentiometry and optical absorption spectrophotometry, respectively. The enthalpies of complexation for two successive complexes, [CaUO2(CO3)3]2− and [Ca2UO2(CO3)3](aq), were determined for the first time by microcalorimetry. The data help to revise the speciation of uranium(VI) species under seawater conditions. In contrast to the previously accepted assumption that the highly negatively charged [UO2(CO3)3]4− is the dominant species, the revised speciation indicates that the dominant aqueous uranium(VI) species under seawater conditions is the neutral [Ca2UO2(CO3)3](aq). The results have a significant impact on the strategies for developing efficient sorption processes to extract uranium from seawater.